PENGELOLAAN BIDANG KESISWAAN OLEH WAKA KESISWAAN DALAM PENGUATAN KOMPETENSI EKSTRAKURIKULER PASKIBRA DI SMP NEGERI 7 SAMARINDA - Rahmah Maulidah Arnanti; Muhammad Jamil; Marwiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the management of student affairs by the Vice Principal of Student Affairs in strengthening the extracurricular competency of Paskibra at SMP Negeri 7 Samarinda. Student competency in extracurricular activities, especially Paskibra, requires effective managerial support to be able to develop optimally. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the Vice Principal of Student Affairs has a strategic role in planning, implementing, and evaluating Paskibra activities. Management is carried out systematically through the preparation of annual programs, routine coaching, and collaboration with extracurricular instructors. Obstacles faced include limited facilities and lack of active student participation, but can be overcome through a collaborative approach and continuous motivation. In conclusion, good management of student affairs contributes significantly to improving student competency in Paskibra activities.